Jasper & Ollie Build a Fort - Willan, Alex (New York : Doubleday Books for Young Readers, 2020)
"Jasper the fox and Ollie the sloth have a fort-building contest in their yard"--
Ages 3-6.
Keywords: Foxes; Fiction; Sloths; Fiction; Building; Fiction; Fiction